Figure 3 from: Lamelas-Lopez L, Ferrante M, Borges PAV, Amorim do Rosário I, Neves V (2023) Nest predation of Cory's shearwater Calonectris borealis (Aves, Procellariiformes) by introduced mammals on Terceira Island, Azores. Biodiversity Data Journal 11: e112871. https://doi.org/10.3897/BDJ.11.e112871 - Lamelas-Lopez, Lucas; Ferrante, Marco; Borges, Paulo; Amorim do Rosário, Isabel; Neves, Veronica (Zenodo, 2023)
Figure 3 Relationship between daily mortality estimate (DME) of Cory`s shearwater nests and log-transformed Relative Abundance Index of black rats (RAI100 Rattus rattus).